Experience of literacy and mathematical literacy with textual genre in a methodological intervention project - Cardoso , Karina Lucia Pires; de Souza, Elenton Oliveira; Manfredo , Elizabeth Cardoso Gerhardt; Oliveira , Emilia Pimenta (Seven Editora, 2023)
This article aims to report an experience of methodological intervention, with the purpose of linguistic and mathematical literacy, from the textual genre supermarket insert, in response to the following concern: how to alphabetize and mathematically literate children from the 1st to the 5th grade of elementary school, through the textual genres that circulate in the various social environments? The interventions took place under the project "Practices of mathematical and scientific literacy in classes from 1st to 5th grade of public schools in Belem-PA", part of the Support Program for Methodological Intervention Projects (PAPIM) of the Pro-Rectory of Graduation of the Federal University of Pará - UFPA. The interventions object of this report was developed with students of the 2nd year of elementary school I, from one of the two public schools of Belem-PA participating in the project. The results obtained indicate possibilities of realization of literacy and mathematical literacy, in an integrated way, having as a teaching instrument the textual genres and, in particular, the supermarket insert.DOI:https://doi.org/10.56238/alookdevelopv1-166